(untitled) (Research, Society and Development, 2022)
The article presents results of a review on studies of biological activity with bryophytes in works carried out between the years 2000 and 2019. For data collection, the bases were used: Science Direct, Scopus and Google Scholar, the descriptors were: “bryophytes antifungal extracts” and “antifungal activities of bryophyte extracts”. As inclusion criteria: articles with bioassays and open access. Exclusion criteria: review articles, chemical profile, books, scientific notes, brief report and work on events. The conservation status of the species was made by searching the website of the International Union for the Conservation of Nature (IUCN). 53 publications were selected, coming from different continents, especially the Asian continent, especially India with a total of 21 publications. Regarding the years of publication, 2011 stands out with 9 publications. Marchantia polymorpha L. was the species with the most studies (seven). Eight species used in the studies are under some degree of threat, especially the Bryum cellulare Hook, classified as In Danger (EN). Research on the biological activity of bryophytes with regard to their antifungal activities is already underway, however all of them from outside Brazil and with little emphasis on America.